2002
DOI: 10.1002/art.10126
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation is preceded by tumor necrosis factor‐dependent infiltration of mesenchymal cells in experimental arthritis

Abstract: Objective. To determine the involvement of mesenchymal progenitor cells in the induction of collageninduced arthritis (CIA).Methods. DBA/1 mice were immunized with type II collagen in adjuvant or adjuvant alone, and the presence of mesenchymal cells in the joints of prearthritic mice was studied by immunohistochemistry.Results. An analysis of the joints on day 10 postimmunization (at least 10 days before the onset of arthritis) revealed synovial hyperplasia without leukocytic infiltration. Large, round cells e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
0
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(112 citation statements)
references
References 20 publications
4
103
0
5
Order By: Relevance
“…Evidence for such an infiltrate has been described in animal models of RA, in which TNF-responsive mesenchymal cells were identified within enlarged bony canals connecting bone marrow to synovium (29). Unfortunately, there are no MRI studies of animal models of early RA, and such studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for such an infiltrate has been described in animal models of RA, in which TNF-responsive mesenchymal cells were identified within enlarged bony canals connecting bone marrow to synovium (29). Unfortunately, there are no MRI studies of animal models of early RA, and such studies are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tumor necrosis factor ␣ and stem cell-derived growth factor 1 may play somewhat similar roles in supporting the erosive synovitis of RA (42,43).…”
Section: Mechanisms Of Autoimmunity and Rituximabmentioning
confidence: 98%
“…33,34 In experimental CIA, MSCs were found in the joints of animals at 2 weeks before the onset of the disease. At that time, synovial hyperplasia was associated to an increase of medullar cells in the epiphyseal region and formation of canals between the bone marrow and the joint cavity.…”
Section: Hematopoietic and Mscs In Autoimmune Diseasesmentioning
confidence: 99%
“…At that time, synovial hyperplasia was associated to an increase of medullar cells in the epiphyseal region and formation of canals between the bone marrow and the joint cavity. 34 Histological analysis suggested that MSCs could migrate from the bone marrow. Up to 2% of the cells stained positively for one marker of MSCs, the bone morphogenetic protein receptor (BMPR)-I, and negatively for the HSC-specific CD34 marker.…”
Section: Hematopoietic and Mscs In Autoimmune Diseasesmentioning
confidence: 99%